Dietary quality and nutrient intake in adults with obsessive–compulsive disorder. Issue 6 (19th November 2021) - Nguyen, Thomas P.; Cribb, Lachlan; Ng, Chee H.; Byrne, Gerard J.; Castle, David; Brakoulias, Vlasios; Blair-West, Scott; Oliver, Georgina; Ee, Carolyn; Dean, Olivia M.; Camfield, David A.; Bousman, Chad; et al.
Abstract : Background: Many mental disorders, including depression, bipolar disorder and schizophrenia, are associated with poor dietary quality and nutrient intake. There is, however, a deficit of research looking at the relationship between obsessive–compulsive disorder (OCD) severity, nutrient intake and dietary quality. Aims: This study aims to explore the relationship between OCD severity, nutrient intake and dietary quality. Method: A post hoc regression analysis was conducted with data combined from two separate clinical trials that included 85 adults with diagnosed OCD, using the Structured Clinical Interview for DSM-5. Nutrient intakes were calculated from the Dietary Questionnaire for Epidemiological Studies version 3.2, and dietary quality was scored with the Healthy Eating Index for Australian Adults – 2013. Results: Nutrient intake in the sample largely aligned with Australian dietary guidelines. Linear regression models adjusted for gender, age and total energy intake showed no significant associations between OCD severity, nutrient intake and dietary quality (all P > 0.05). However, OCD severity was inversely associated with caffeine (β = −15.50, 95% CI −28.88 to −2.11, P = 0.024) and magnesium (β = −6.63, 95% CI −12.72 to −0.53, P = 0.034) intake after adjusting for OCD treatment resistance. Conclusions: This study showed OCD severity had little effect on nutrient intake and dietary quality. Dietary quality scores were higher than prior studies with healthy samples, but limitations must be noted regarding comparability. Future studies employing larger sample sizes, control groups and more accurate dietary intake measures will further elucidate the relationship between nutrient intake and dietary quality in patients with OCD.